The association between pitch accuracy and batter outcomes in Major League Baseball - Napoli, B; Napoli, D; Napoli, A; Lin, T; Robertson, M; Machan, J; Baird, J. (The Sport Journal, 2025)
Purpose: Pitch speed is considered synonymous with pitching success. In years past, the accuracy of a pitch was paramount but in recent years this has been deprioritized as compared with pitch speed. Over the years, batters have adapted to higher pitching speeds so pitch strategy and placement may be more important. Our hypothesis was that pitching accuracy associated with intended pitch location would be a significant factor in pitching success in Major League Baseball (MLB).